2002
DOI: 10.1128/jvi.76.20.10427-10436.2002
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus-Induced Changes in B-Lymphocyte Gene Expression

Abstract: In primary Epstein-Barr virus (EBV) infection, a substantial fraction of peripheral blood B lymphocytes are latently infected and express virus-encoded proteins that are capable of causing continuous B-cell proliferation. The EBV-encoded proteins engender an unusually vigorous and large T-cell immune response which eliminates most of the virus-infected cells. In severely T-cell immune-compromised or otherwise susceptible people, the EBV-infected B lymphocytes can malignantly proliferate (reviewed in reference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
108
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(119 citation statements)
references
References 126 publications
10
108
0
1
Order By: Relevance
“…This form of latency is termed Latency III. This form of latency is common in immunoblastic lymphomas [17]. A Type II form of latency where EBNA 1, LMP-1 and LMP-2a are expressed has been identified in some EBV associated lymphomas.…”
Section: Subtypes Of Aids Nhlsmentioning
confidence: 99%
See 2 more Smart Citations
“…This form of latency is termed Latency III. This form of latency is common in immunoblastic lymphomas [17]. A Type II form of latency where EBNA 1, LMP-1 and LMP-2a are expressed has been identified in some EBV associated lymphomas.…”
Section: Subtypes Of Aids Nhlsmentioning
confidence: 99%
“…The most commonly identified virus associated with AIDS related lymphomas is EBV and there is a large body of published work on the oncogenic mechanisms of this agent [17,18]. B-lymphocytes transformed by EBV (lymphoblastoid cell lines) in vitro express an array of virus-encoded proteins including six EBV nuclear antigens (EBNAs) and three LMPs.…”
Section: Subtypes Of Aids Nhlsmentioning
confidence: 99%
See 1 more Smart Citation
“…The six human B-lymphoma cell lines used in this study are as follows: BJAB, EBV-negative, GCB-like DLBCL (20,21); SUDHL-4, a B-lymphoma that has been characterized as both a follicular lymophoma (22) and GCBlike DLBCL (23); BL-41, EBV-negative Burkitt lymphoma (14); Daudi, EBV-positive, LMP1-negative Burkitt lymphoma (24); IB4, EBV-transformed lymphoblastoid cell line (14); and RC-K8, ABC-like DLBCL (25). For treatment of cells with lipopolysaccharide (LPS) (Sigma), BJAB cells were first cultured in DMEM containing 5% FBS for 24 h and then treated with 5 g/ml of LPS for the indicated times.…”
Section: Methodsmentioning
confidence: 99%
“…We previously showed that overexpression of an activated mutant of the NF-B family transcription factor REL in the GCB-like B-lymphoma cell line BJAB leads to reduced expression of CD10 (13). Infection of cells with Epstein-Barr virus (EBV) or human cytomegalovirus, both inducers of NF-B, causes reduced expression of CD10 (14,15). Taken together, such results suggested to us that NF-B or a target of NF-B is involved in repressing CD10 gene/protein expression in certain B-cell lymphomas.…”
mentioning
confidence: 99%